SISTEM MONITORING PH DAN SUHU AIR MENGGUNAKAN APLIKASI BLYNK DI KOLAM BUDIDAYA IKAN KOI PROKLAMATOR BLITAR, JAWA TIMUR - Irfan Zuhri; Hadi Suyono; n/a Nurussa’adah (Jurnal Mahasiswa TEUB, 2023)
The quality of pond water is very important for the successful cultivation of koi fish. The survival rate and growth of the fish are highly dependent on the water quality. If there are any changes in temperature or pH levels, the koi fish can become stressed and even die. The optimal temperature for the growth of koi fish is between 25°C - 30°C, while the optimal pH range is between 6.5 - 8.5. A monitoring system is used to measure the water quality of the koi fish using temperature and pH sensors, and the data is measured in real-time using the Internet of Things (IoT) to obtain good water quality and ideal temperature and pH values. With the Internet of Things (IoT), data can be sent and received quickly, taking about 0.5 seconds from the sender to the receiver, even if the distance is far as long as it is connected to the internet. This data is then sent to the Blynk server and can be displayed through the Blynk application on an Android device. If the water quality is not ideal, information will be sent to the koi fish cultivator's Android smartphone in the form of notifications on the Blynk server. Keywords: Water Quality, Koi Fish, Temperature, pH, Internet of Things (IoT) DAFTAR PUSTAKA[1] Firmansyah, Z. A. (2019). Monitoring Kualitas Air Kolam Pembenihan Ikan Koi Berbasis Internet of Things.[2] Korespondensi, Bersih, J., Tengah, K., Cibinong, K., Perikanan, D., Peternakan, D., Dwi Nugroho, B., Hardjomidjojo, H., Ma’mun Sarma, D., & Tengah, K. (2017). Strategi Pengembangan Usaha Budidaya Ikan Konsumsi Air Tawar dan Ikan Hias Air Tawar pada Kelompok Mitra Posikandu Kabupaten Bogor Business Expansion Strategies on Consumable Freshwater Fish and Decorative Fish Breeding in Kelompok Mitra Posikandu Bogor District (Vol. 12, Issue 2). http://journal.ipb.ac.id/index.php/jurnalmpi/[3] Ritonga, L. B., & Indah Sari, L. (n.d.). Pembenihan Ikan Koi (Cyprinus carpio) Secara Alami Di Mina Sumber Utama KoiFish Hatchery of Koi (Cyprinus carpio) In Mina Sumber Utama Koi. https://doi.org/10.15578/chanos.v20i2.1198 2[4] Saloh, A. Y., Aida, Y., & Zahida, F. (2005). Penambahan Tepung Cangkang Udang dalam Pakan Buatan Sebagai Penguat Warna Ikan Koi (Cyprinus carpio L.). X(1), 59–65.[5] Wantimpres. (2017, April 27). Potensi Perikanan Indonesia.